2018
DOI: 10.1039/c8mt00269j
|View full text |Cite
|
Sign up to set email alerts
|

The cellular economy of the Saccharomyces cerevisiae zinc proteome

Abstract: Zinc is an essential cofactor for many proteins. A key mechanism of zinc homeostasis during deficiency is “zinc sparing” in which specific zinc-binding proteins are repressed to reduce the cellular requirement. In this report, we evaluated zinc sparing across the zinc proteome of Saccharomyces cerevisiae. The yeast zinc proteome of 582 known or potential zinc-binding proteins was identified using a bioinformatics analysis that combined global domain searches with local motif searches. Protein abundance was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 84 publications
(102 reference statements)
2
74
0
Order By: Relevance
“…Despite the increase in RNA abundance, however, the level of Hnt1‐GFP protein decreased ~4‐fold in deficient cells (Figure b). These results are consistent with a recent proteomics analysis that showed that native Hnt1 protein levels decrease from ~30,000 copies per cell in replete conditions to ~6,000 copies in zinc‐deficient cells (Wang et al, ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Despite the increase in RNA abundance, however, the level of Hnt1‐GFP protein decreased ~4‐fold in deficient cells (Figure b). These results are consistent with a recent proteomics analysis that showed that native Hnt1 protein levels decrease from ~30,000 copies per cell in replete conditions to ~6,000 copies in zinc‐deficient cells (Wang et al, ).…”
Section: Resultssupporting
confidence: 92%
“…Hnt1 has a conserved zinc‐binding domain, so its reduced expression may be a zinc‐sparing response to reduce the zinc requirement of zinc deficient cells (Jung et al, ). The abundance of Hnt1 decreases markedly during deficiency (Wang et al, ). Moreover, members of the broader histidine triad superfamily have been implicated in zinc homeostasis suggesting a possible role for Hnt1 in these processes (Moulin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…With MCHM treatment, Yke4 protein levels increased 20%. 582 proteins are predicted to bind protein with 20 proteins binding 90% of total cellular zinc (46) and zinc sparing ensures that essential Zn binding proteins have zinc. As YJM789 expresses less Zrt1 protein normally (24), perhaps the internal levels of zinc and the ability of the yeast to quickly redistribute the zinc in MCHM may alter their ability to grow.…”
Section: Discussionmentioning
confidence: 99%
“…Excess zinc stored in the vacuole, and when needed Zrt3 transports zinc to the cytoplasm. In addition to the vacuole, the ribosome (red circles) bind 20% of total cellular zinc(46). Yke4 is the transmembrane transporter at the ER (pink and purple) that transports zinc in both directions.…”
mentioning
confidence: 99%
“…Further investigations with the yeast model began to address the effects of zinc deficiency on the zinc proteome. They showed that transcriptional regulation results in a lower abundance of zinc proteins and that many zinc enzymes are made but not metalated or perhaps mis-metalated [143]. It remains unknown whether kinetic or thermodynamic factors determine the re-distribution of zinc and whether a functional hierarchy exists and is managed by a triage process that prioritizes the allocation of zinc.…”
Section: Zinc Deficiency a Pro-oxidant Condition Causing Oxidative Smentioning
confidence: 99%